Nonlinear model identification of a shock absorber dynamics - Ridhuan Siradj , Fadly Jashi Darsivan; Hamid, Mohd. Helmi; Abdullah, Mohamad Fahmi (Eastern Mediteranean Academic Research Centre, 2013)
The paper discusses on the technique of modeling a nonlinear dynamics of a commercially available automotive shock absorber. The damper was tested on the damper test bench to obtain its dynamic characteristics. The characteristics include the force-displacement and the force-velocity diagrams. From the result obtained experimentally it clearly showed that the automotive damper behaves nonlinearly. The plot also indicates the hysteresis of the damper at different frequency levels. From the force-velocity graphs a backbone model was then developed and plot. Based on this graph three types of non-parametric model namely the linear model, polynomial model and the power model were then obtained through curve fitting method. The models were then verified by using another set of experimentally obtained data. Based on these models quarter car simulations were conducted. From the simulation it was clear that the linear model showed a large difference in terms of vertical displacement of the sprung mass at the natural frequency compared to the polynomial and the power models.